Informasi dari Feses dan Jejak Kaki Rusa Sambar (Cervus unicolor) serta Implikasinya pada Akurasi Penaksiran Populasi - Rachmat Budiwijaya Suba; Chandradewana Boer; Irman Irman (Jurnal Ilmu Kehutanan, 2010)
Information from Feces and Foot Tracks of Sambar Deer(Cervus unicolor), and Its Implication on PopulationEstimationThis study aims to investigate Sambar Deer (Cervus unicolor) ecology from the encounter of pellet piles groups and tracks in the study area. This study was carried out in Swanslutung village, one of the villages in the Paser District, East Kalimantan, where the hunting pressure is still relatively high and local people still depend on hunting for bush-meat of Sambar Deer. Further discussion addresses to find accurate and reliable scheme of population etimate. Average density estimate for the study area, based on the groups of pellet piles count, was 3.01 + 0.17 individuals/km2. Tracks can give information about sex and age classes, some of essential parts to study population dynamic of Sambar Deer. Dispersion of pellet piles groups and tracks can be used in tracking to study home range and territories of the species.